2023
DOI: 10.1287/mnsc.2022.4327
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19 on U.S. Small Businesses: Evidence from Owners, Managers, and Employees

Abstract: We analyze a large-scale survey of small business owners, managers, and employees in the United States to understand the effects of the COVID-19 pandemic on those businesses. We explore two waves of the survey that were fielded on Facebook in April 2020 and December 2020. We document five facts about the impact of the pandemic on small businesses. (1) Larger firms, older firms, and male-owned firms were more likely to remain open during the early stages of the pandemic with many of these heterogeneities persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Thus, leveraging the job transition literature to understand how employees are successfully navigating the return to work would be useful. Likewise, our review revealed that certain employees (e.g., women, parents, Asian;Alekseev et al, 2022;Jun & Wu, 2021;Leroy et al, 2021) may be differentially affected by the pandemic. Such disparate outcomes may continue after the pandemic.…”
Section: Organizational Decisionsmentioning
confidence: 80%
See 4 more Smart Citations
“…Thus, leveraging the job transition literature to understand how employees are successfully navigating the return to work would be useful. Likewise, our review revealed that certain employees (e.g., women, parents, Asian;Alekseev et al, 2022;Jun & Wu, 2021;Leroy et al, 2021) may be differentially affected by the pandemic. Such disparate outcomes may continue after the pandemic.…”
Section: Organizational Decisionsmentioning
confidence: 80%
“…Specifically, female managers with children (especially young children) generated a monthly average of 9% lower returns in the shock month of school closures. Although many studies have suggested that COVID-19 had a disproportionate effect on women's well-being due to increased work-family boundary permeations and work-family conflict (e.g., Alekseev et al, 2022;Leroy et al, 2021;Shockley, Gabriel, et al, 2021), this finding is significant because it quantifies the cost of lost childcare. Sergent and Stajkovic (2020) found that gender influenced how effectively state leaders (i.e., governors) in the United States managed their states' responses to the pandemic.…”
Section: Leaders and The Pandemicmentioning
confidence: 99%
See 3 more Smart Citations